2018
DOI: 10.1371/journal.pone.0193595
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effect of polyamines on In vitro gene expression: Enhancement at low concentrations but inhibition at high concentrations

Abstract: BackgroundPolyamines have various biological functions including marked effects on the structure and function of genomic DNA molecules. Changes in the higher-order structure of DNA caused by polyamines are expected to be closely related to genetic activity. To clarify this issue, we examined the relationship between gene expression and the higher-order structure of DNA under different polyamine concentrations.Principal findingsWe studied the effects of polyamines, spermidine SPD(3+) and spermine SP(4+), on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 32 publications
13
44
0
Order By: Relevance
“…The addition of Na + or K + to the solution tends to increase the luminescence intensity, and K + has a greater enhancing effect, except in experiments with 1.5 mM SPD. The complete inhibition at 1.5 mM SPD is attributable to the transition of the higher-order structure to a tightly packed state, as suggested previously [21,22]. The enhancement of gene expression in the presence of K + has been confirmed at different SPD concentrations as revealed in S1 Fig. To shed light on the effects of Na + and K + on the higher-order structure of DNA in the presence of different concentrations of SPD, we performed real-time single-molecule observation of T4 DNA fluctuating in aqueous solution by using fluorescence microscopy (FM).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The addition of Na + or K + to the solution tends to increase the luminescence intensity, and K + has a greater enhancing effect, except in experiments with 1.5 mM SPD. The complete inhibition at 1.5 mM SPD is attributable to the transition of the higher-order structure to a tightly packed state, as suggested previously [21,22]. The enhancement of gene expression in the presence of K + has been confirmed at different SPD concentrations as revealed in S1 Fig. To shed light on the effects of Na + and K + on the higher-order structure of DNA in the presence of different concentrations of SPD, we performed real-time single-molecule observation of T4 DNA fluctuating in aqueous solution by using fluorescence microscopy (FM).…”
Section: Resultssupporting
confidence: 82%
“…Recently, we have reported that polyamines can either enhance or inhibit gene expression depending on their concentration [21,22]. In our study on the effects of polyamine on gene expression, we observed that, in the presence of polyamine, K + enhances gene expression in vitro much more strongly than Na + .…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations